Pałac Działyńskich. Rozkład dzienny posiłków i ich cena, 10.luty 1874 - 13.marca 1874 (1874)
Książka zestawień.
Brak k.tyt.
Keywords: Kucharstwo; Poznań; Pałac Działyńskich; Kórnik; majętność kórnicka; Majętność Kórnicka. II |Akta administracyjno-gospodarcze